Analysis of Factors Affecting Customer Loyalty on CV Riau Building Pekanbaru - Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Renaldo, Nicholas; Purnama, Intan; Jessen, Jessen; Suranto, Agung (International Conference on Business Management and Accounting, 2024)
This study aims to partially and simultaneously analyze the effect of customer satisfaction, product quality, and price on customer loyalty at CV Riau Bangunan Pekanbaru. This study uses multiple linear regression analysis using the SPSS version 21 application, with a sample of 100 customers at CV Riau Bangunan Pekanbaru. The results of the research overall variable customer satisfaction and product quality affect customer loyalty at CV Riau Bangunan Pekanbaru. At the same time, price has a negative effect on customer loyalty at CV Riau Bangunan Pekanbaru. Customer satisfaction, product quality, and price have contributed 81.7% to the customer loyalty variable, although there is still an 18.3% influence on other factors not included in the study.